Genome-wide characterization and evolutionary analysis of linker histones in castor bean (Ricinus communis) - Guo, Jiayu; Li, Ping; Yu, Anmin; Chapman, Mark A.; Liu, Aizhong (Frontiers in Plant Science, 2022)
H1s, or linker histones, are ubiquitous proteins in eukaryotic cells, consisting of a globular GH1 domain flanked by two unstructured tails. Whilst it is known that numerous non-allelic variants exist within the same species, the degree of interspecific and intraspecific variation and divergence of linker histones remain unknown. The conserved basic binding sites in GH1 and evenly distributed strong positive charges on the C-terminal domain (CTD) are key structural characters for linker histones to bind chromatin. Based on these features, we identified five linker histones from 13 GH1-containing proteins in castor bean (Ricinus communis), which were named as RcH1.1, RcH1.2a, RcH1.2b, RcH1.3, and RcH1.4 based on their phylogenetic relationships with the H1s from five other economically important Euphorbiaceae species (Hevea brasiliensis, Jatropha curcas, Manihot esculenta, Mercurialis annua, and Vernicia fordii) and Arabidopsis thaliana. The expression profiles of RcH1 genes in a variety of tissues and stresses were determined from RNA-seq data. We found three RcH1 genes (RcH1.1, RcH1.2a, and RcH1.3) were broadly expressed in all tissues, suggesting a conserved role in stabilizing and organizing the nuclear DNA. RcH1.2a and RcH1.4 was preferentially expressed in floral tissues, indicating potential involvement in floral development in castor bean. Lack of non-coding region and no expression detected in any tissue tested suggest that RcH1.2b is a pseudogene. RcH1.3 was salt stress inducible, but not induced by cold, heat and drought in our investigation. Structural comparison confirmed that GH1 domain was highly evolutionarily conserved and revealed that N- and C-terminal domains of linker histones are divergent between variants, but highly conserved between species for a given variant. Although the number of H1 genes varies between species, the number of H1 variants is relatively conserved in more closely related species (such as within the same family). Through comparison of nucleotide diversity of linker histone genes and oil-related genes, we found similar mutation rate of these two groups of genes. Using Tajima’s D and ML-HKA tests, we found RcH1.1 and RcH1.3 may be under balancing selection.